RESEARCH ON THE EMERGING BAZAAR TOURISM MODEL AND LOCAL ECONOMIC DEVELOPMENT IN CHINA - Quan, Liang (University Research Base, 2025)
Under the dual impact of urbanization and the digital economy, contemporary bazaar in China have transformed from a singular economic function to a diversified and composite form, gradually incorporating emotional connections, social relationships, and cultural heritage. Particularly, through the "market + tourism" model, bazaar-type economy have achieved functional upgrades. This paper employs comprehensive methods such as literature review and case study analysis to explore the interactive mechanisms between bazaar and cultural tourism. The research findings are as follows: First, driven by operational innovation, government promotion, and consumption upgrading, markets have continuously evolved, forming five primary bazaar tourism types—rural traditional market-based, traditional cultural revitalization-based, nighttime economy-driven, rural revitalization-empowered, and youth creativity-aggregated. Second, by developing experiential tourism economies, bazaars have established a new "economic-cultural-emotional" ecosystem. Third, the material form of bazaar has evolved from traditional stalls to cultural-tourism complexes, significantly boosting local economic development and labor employment.